Opioidergic modulation of monetary incentive delay fMRI responses - Samuel Turton; Peter C.T. Hawkins; Christopher Muller-Pollard; Evangelos Zois; Patricia Conrod; Fernando Zelaya; Mitul A. Mehta (Psychopharmacology, 2025)
Rationale It is hypothesised that modulation of striatal dopaminergic signalling plays a key role in the rewarding effects of opioids. The monetary incentive delay (MID) task is a functional magnetic resonance imaging (fMRI) paradigm used to investigate striatal responses, which may reflect striatal dopamine release, during the anticipation of a financial reward. Objectives We hypothesised that fentanyl would modulate striatal MID task Blood Oxygenation Level Dependent (BOLD) responses, reflecting opioidergic modulation of striatal dopaminergic signalling. Methods 24 right-handed males who undertook four MRI scanning sessions, during which they completed an MID task 15 min after receiving an intravenous infusion of either one of two doses of fentanyl (50 µg/70kg), naloxone (400 µg) or placebo (saline 0.9%), were included in the analyses. End tidal CO 2 data were collected to control for respiratory depression. Results We demonstrated fentanyl induced increases in MID task reward and loss anticipation BOLD compared with placebo and naloxone in both region of interest (ROI) and whole brain analyses. These results were in cortical regions including the lingual gyrus, precuneus, posterior cingulate and frontal pole rather than the striatum. Conclusions Our results show the primary effects of fentanyl on MID anticipation BOLD in regions associated with the preparation of a motor response to a salient visual cue, rather than in regions typically associated with reward processing such as the striatum. This suggests that opioid agonists do not affect striatal activation during the MID task. Tasks using naturalistic rewards, for example feeding, sex or social contact which induce endogenous opioid signalling, may be more appropriate to probe the effects of fentanyl on reward processing. These results are from male participants’ data and therefore may not be generalisable to female participants.